The making of self and world in advertising - Waide, John (Journal of business ethics, 1987)
In this paper I will criticize a common practice I call associative advertising. Briefly, associative advertising induces people to buy (or buy more of) a product by associating that market product with such deep-seated non-market goods as friendship, acceptance and esteem from others, excitement and power even though the market good seldom satisfies or has any connection with the non-market desire. The fault in associative advertising is not that it is deceptive or that it violates the autonomy of its audience — on this point I find Robert Arrington's arguments persuasive (‘Advertising and Behavior Control’, Journal of Business Ethics 1 (1982), 3–12). Instead, I will argue against associative advertising by examining the virtues and vices at stake. In so doing, I will offer an alternative to Arrington's exclusive concern with autonomy and behavior control., My main criticism is two-fold: (a) Advertisers must surely desensitize themselves to the compassion, concern, and sympathy for others that are central emotions in a virtuous person, and (b) associative advertising influences its audience to neglect the nonmarket cultivation of our virtues and to substitute market goods instead, with the result that we become worse and, quite likely, less happy persons.